Hemocytes of the mud crab Scylla paramamosain: Cytometric, morphological characterization and involvement in immune responses. Issue 72 (January 2018) - Zhou, Yi-Lian; Gu, Wen-Bin; Tu, Dan-Dan; Zhu, Qi-Hui; Zhou, Zhong-Kai; Chen, Yu-Yin; Shu, Miao-An
Abstract: Hemocytes play essential roles in the innate immune system of crustaceans. Characterization of hemocytes from estuary mud crab Scylla paramamosain was performed by flow cytometry and morphological studies such as cytochemical staining and electron microscopy. The hemocyte subsets were further separated using a modified Percoll density gradient centrifugation method. Based on the morphological characteristics of the cells, three distinct categories of hemocytes were identified: granulocytes with abundant large granularity representing 5.27 ± 0.42%, semigranulocytes with small or less granularity representing 76.03 ± 3.34%, and hyalinocytes (18.70 ± 3.92%) which were almost no granularity. The total hemocyte cell count and the percentage of hemocyte subsets varied after pathogen infection, including Vibrio alginolyticus and the viral double-stranded RNA analog Poly (I:C). The phagocytic process is of fundamental importance for crustaceans' cellular immune response as well as development and survival. The results of the in vitro phagocytosis assays analyzed by flow cytometry demonstrated that granulocytes and semigranulocytes had significantly higher phagocytic ability than hyalinocytes. A primary culture system, L-15 medium supplemented with 5–10% fetal bovine serum, was developed to further investigate the immune function of hemocytes. Furthermore, adenovirus can be utilized to effectively transfer GFP gene into hemocytes. Overall, three hemocyte sub-populations of S. paramamosain were successfully discriminated, moreover, their response to pathogen infections, phagocytic activity and adenovirus mediated transfection were also investigated for the first time. This study may contribute to a better understanding of the innate immune system of estuary crabs. Highlights: Hemocytes from S. paramamosain were characterized by cytochemical staining, electron microscopy and flow cytometry. The cell count and the proportion of hemocytes varied differently after different pathogen infections. Phagocytosis of bacteria was primarily executed by granulocytes and semigranulocytes. L-15 medium supplemented with 10% FBS was the optimal condition for semigranulocytes primary culture. Adenovirus could be employed to transfer foreign genes into crustacean hemocytes.